A Systematic Review of Mobile-Assisted Vocabulary Learning and Teaching in ESL/EFL context - Nawaz, Muhammad; Ganapathy, Malini N. G.; Manzoor, Sadaf; Ezzy, Tess; Farooqi, Shahzad Ul Hassan (UUM Press, 2025)
Purpose - The integration of mobile technology in ESL/EFL contexts has garnered significant attention from contemporary researchers, teachers, and learners due to the advancements in technology, dynamic features, and multimodal applications. With this growing interest, there is a need to synthesize the existing literature and identify current trends in the field. Methodology - This study reviewed research on mobile-assisted second language (L2) vocabulary learning and teaching through two approaches. First, a bibliometric analysis was employed to provide a comprehensive overview of the field, encompassing 774 publications retrieved from the Scopus database. Second, 20 empirical articles were analyzed to determine technological and pedagogical trends in MAVL studies. Findings - The analysis identified the most frequently used keywords, influential authors, and the most productive countries in MAVL research. Key areas of focus in L2 vocabulary learning and teaching included learners’ performance and perceptions, with gamification emerging as a predominant technological feature in recent empirical studies Significance - Although the findings are preliminary, they offer valuable insights for conducting future research, emphasizing emerging trends and unexplored areas within MAVL